Peripheral Regional Anesthesia for Awake Emergency Upper Limb Trauma Surgery in an Adult Patient With Fontan Physiology - Patrick N. Wiseman; Molly Featherstone; Noreen Dowd; Aislinn Sherwin (Case Reports in Anesthesiology)
Conclusions: This case report and ensuing discussion highlight the benefits which regional anaesthesia can provide for adult patients with complex cardiac physiology, including Fontan circulation, undergoing noncardiac surgery when compared to general anaesthesia.